Inspired finance : the role of faith in microfinance and international economic development - Looft, Michael (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
Argues that much of the world's poor need access to financial services through vehicles such as microfinance rather than a continued reliance on charity. It demonstrates how modern microfinance traces its roots to various religious traditions, exploring the tension between charity and self-reliance in those traditions.
Includes bibliographical references and index.
oif 11/06/15, ijb 26/02/2019
Loan
Keywords: Finance; Microfinance; Charities; Poverty; Economic development